Optimal resource management with the multiple goals of citrus-based farming systems at farm and watershed levels, Chinag Mai Province - Panitpim Sittisak (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objectives of this study were to find the optimal resource management with the multiple goals of citrus-based farming systems in the Fang watershed at the farm and the watershed levels and to find the relationships and trade-offs between the natural resource management at the farm and the watershed levels. The citrus farms in this study were divided into four types: small farms using chemicals (SFC), small farms using chemicals and bioextract (SFCB), large farms using chemicals (LFC) and large farms using chemicals and bioextract (LFCB). A set of questionnaires was designed for data collection covering 149 households in Chai Prakan, Fang and Mae Ai districts, Chiang Mai province. The study used a multiple goal linear programming model at the farm level which contained 80 decision variables and 64 constraints. The watershed level model contained 84 decision variables and 67 constraints. The models have 3 sets of goals: economic, social and environmental. These were further broken down into 7 goals at the farm level, and 8 goals at the watershed level. An analysis using multiple-goal programming was conducted by weighting the goals using analytic hierarchy process (AHP) method. The study used the IMGP-LPlan software program.